Activation of epithelial cells by the major kiwifruit allergen Act d 1 in human and mouse-derived intestinal model. (November 2019) - Nešić, Andrijana; Stam, Annemarie; Čavić, Milena; Ten Klooster, Jean Paul; Pieters, Raymond; Smit, Joost; Gavrović-Jankulović, Marija
Graphical abstract: Highlights: Act d 1 up-regulates tight junction proteins in Caco-2 monolayers. Act d 1 up-regulates tight junction proteins in 2-Dimensional intestinal organoids. Act d 1 induces release of proinflamatory cytokines in 2D organoids and Caco-2 cells. Act d 1 impaired TJs network of E-cadherin, claudin-3 and ZO-1 in 2D-organoids. 2D mouse organoids are a promising model for assessment of intestinal cell response. Abstract: In this study, two intestinal models were employed to assess the modulatory potential of a major kiwifruit allergen on the innate immunity of epithelial cells. Effects of Act d 1 were analyzed in terms of gene expression and structural changes of tight junction (TJ) proteins, as well as up-regulation of pro-inflammatory cytokines in Caco-2 cells and, for the first time, in mouse-derived intestinal 2-dimensional (2D) organoids. Biologically active Act d 1 induced up-regulation of TJ genes for CLDN-2, CLDN-3, CLDN-4, ZO-1, and on the protein level induced release of pro-inflammatory cytokines IL-1β, TNFα and IL-33 in both employed model systems. In 2D-organoids, active Act d 1 impaired the TJ protein networks of E-cadherin, claudin-3, and ZO-1. 2D-organoids generated from mouse intestine are a promising new model system for the assessment of allergen-induced intestinal cell responses and a useful tool for mitigation of risks associated with novel food proteins.